2021
DOI: 10.3389/fneur.2021.598632
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Spindle Characteristics in Obstructive Sleep Apnea Syndrome (OSAS)

Abstract: Background: We compared the density and duration of sleep spindles topographically in stage 2 and 3 of non-rapid eye movement sleep (N2 and N3) among adults diagnosed with Obstructive Sleep Apnea Syndrome (OSAS) and healthy controls.Materials and Methods: Thirty-one individuals with OSAS (mean age: 48.50 years) and 23 healthy controls took part in the study. All participants underwent a whole night polysomnography. Additionally, those with OSAS were divided into mild, moderate and severe cases of OSAS.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 58 publications
3
21
1
Order By: Relevance
“…Sleep efficiency decreased in an almost linear fashion from healthy controls to individuals with mild, moderate, and severe OSA [33], with individuals with severe OSA having the lowest sleep efficiency, compared to individuals with no, mild, and moderate OSA, and always assessed with sleep-EEG. In parallel, arousal index and wake index were highest in individuals with moderate and severe OSA, compared to individuals with no and mild OSA [33].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Sleep efficiency decreased in an almost linear fashion from healthy controls to individuals with mild, moderate, and severe OSA [33], with individuals with severe OSA having the lowest sleep efficiency, compared to individuals with no, mild, and moderate OSA, and always assessed with sleep-EEG. In parallel, arousal index and wake index were highest in individuals with moderate and severe OSA, compared to individuals with no and mild OSA [33].…”
Section: Introductionmentioning
confidence: 93%
“…Foroughi et al [37] reported in their brief review the following predictors: snoring, male gender, age over 50 years, hypertension, and metabolic diseases. To our knowledge, except the recently published data on sleep spindles among individuals with OSAS [33], PSG data in combination with demographic and anthropometric information of Iranian individuals with OSA are missing. To counter this, in the present study, we blended demographic, anthropometric, and PSG data to predict OSA severity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous small studies consistently reported decreased overall spindle density (11)(12)(13)(14)(15)(16) Hz, number/min), frontal slow spindle density (11)(12)(13) Hz, number/min), centroparietal fast spindle density (13)(14)(15)(16) Hz, number/min), and overall spindle frequency in clinical samples of patients with OSA compared to age-or gender-matched controls [4,[10][11][12]. Some evidence also suggests spindle abnormalities partly improve with OSA therapy [12,13].…”
Section: Introductionmentioning
confidence: 95%
“…Some evidence also suggests spindle abnormalities partly improve with OSA therapy [12,13]. Furthermore, several small studies showed associations of a greater number of obstructive breathing episodes with reduced spindle deceleration and decreased spindle density [14][15][16].…”
Section: Introductionmentioning
confidence: 99%